1991
DOI: 10.3109/02656739109004992
|View full text |Cite
|
Sign up to set email alerts
|

Histopathology of prostatic tissue after transurethral hyperthermia

Abstract: Histopathological changes were studied in four patients who had moderate to severe urinary outflow obstruction due to benign prostatic hyperplasia (BPH) and were treated with transurethral microwave hyperthermia (TUMH). All these patients received TUMH with a helical antenna using a BSD 300 unit. The temperature was controlled on the urethral surface at 45 degrees C +/- 1 degree C. Each treatment session lasted 70 min at this temperature. Histological changes were periurethral, extending up to 6 mm radially an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
15
0

Year Published

1991
1991
2003
2003

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 37 publications
(16 citation statements)
references
References 14 publications
1
15
0
Order By: Relevance
“…Since prostatic heating to less than 45°C cannot create permanent tissue change [7,14], TUMT was thus designed to achieve a therapeutic temperature of more than 45°C within the prostate for a treatment response. Despite the maximal intraprostatic temperature of 47.8 B 1.12°C that we were able to achieve in this study, the average radiometer temperature was only 41.6 B 1.78°C which may indicate that the duration of the effective therapeutic temperature is not long enough, and, therefore, the treatment became less effective.…”
Section: Discussionmentioning
confidence: 99%
“…Since prostatic heating to less than 45°C cannot create permanent tissue change [7,14], TUMT was thus designed to achieve a therapeutic temperature of more than 45°C within the prostate for a treatment response. Despite the maximal intraprostatic temperature of 47.8 B 1.12°C that we were able to achieve in this study, the average radiometer temperature was only 41.6 B 1.78°C which may indicate that the duration of the effective therapeutic temperature is not long enough, and, therefore, the treatment became less effective.…”
Section: Discussionmentioning
confidence: 99%
“…FT-IR spectroscopy has been extensively applied to study the secondary structure of biological samples [20][21][22], Although thermotherapy or hyperthermia was suc cessfully used in BPH therapy, histological evidence and pathological lesions consisting of inflammatory edema, hemorrhagic vascular lesions with coagulative necrosis, glandular and smooth muscle necrosis have been reported [23]. However, basic studies on the conformational changes in the protein structure of BPH tissue are scant.…”
Section: Discussionmentioning
confidence: 99%
“…A reduction was observed in the edematous reaction after a period of 2-3 weeks, with a collagen deposit progressively replacing the necrotic tissue and process of neoangiogenesis at the periphery of the lesion [15]. The coagulative necrosis of the transition area has a characteristic butterfly shape (parallel to that of the isothermic distribution curve) that forms the distinctive differentiation line of the HE-TUMT from the microwave or radiofrequency hyperthermia, the techniques causing at most superficial necrosis of the urethra or small randomly distributed areas of coagulation in the transition area [16]. In a European multicentric study in 1996, transrectal prostatic ultrasound showed cavitation in the transition area in 37% of patients undergoing HE-TUMT.…”
Section: Discussionmentioning
confidence: 99%